Supplementary Vocational Education of Academic Staff: Opportunities and Problems of Implementation - P. A. Ambarova; G. E. Zborovsky (Высшее образование в России, 2024)
The article deals with the problem of the involvement of academic staff (AS) of universities in the system of continuing education. The subject of the study is the possibilities and problems of supplementary vocational education (SVE) for academic staff of Russian universities. Based on the materials of statistics and analysis of documents (university development programs, regulations on advanced training), the objective aspects of the functioning of the university system of AS supplementary vocational education have been studied. The subjective aspects of obtaining supplementary vocational education are revealed on the basis of materials from semi-structured interviews with AS of universities of the Ural Federal District. The motivation for obtaining SVE, the needs for specific content and types of training, financing, and organizational conditions are analyzed. The key problems of the academic segment of the SVE system are revealed: reduction of the state financing of the costs of universities for the training of AS; commercialization of the university SVE system; the lack of guaranteed quality and diversity of SVE programs for AS; unsatisfactory organizational conditions for SVE of AS; inflexibility of the continuing education system in terms of taking into account the results of AS training. In a practical sense, the identified problems are directions for changes in the state and university policy of professional development of the AS in the context of the implementation of higher education development programs